Dynamic Identification of an Early 20th Century Civil Architectural Building - BaÄŸbancÄ±, Bilal Muhammed (Civil Engineering Journal, 2020)
Historical structures are important in terms of both original construction techniques and cultural heritage. Therefore, material properties, construction techniques and dynamic behaviors of these structures must be identified in order to preserve them in the future by restoration studies.Â  This study is aimed to serve as an example for similar buildings in the region whose walls were constructed using filled brick with lime mortar and constructed using both timber and reinforced concrete slabs. In this study, the plan layout, construction techniques and the material usage of the building were investigated in detail. The mechanical and dynamic properties such as compressive stress, elastic moduli, shear stress, natural frequencies and mode shapes of the building were determined in-situ by flat-jack, shear and vibration tests. The finite element model of the structure was prepared, and the modal analysis of the structure was performed. The calibration of the model was ensured according to the vibration test results. The results obtained from this study show us that in-situ tests are extremely important for the accuracy of finite element models. It has been determined that the mechanical test data can be used with over 80% success in finite element models.